2019
DOI: 10.2147/cmar.s197245
|View full text |Cite
|
Sign up to set email alerts
|

<p>Radiotherapy for patients with completely resected pathologic IIIA(N2) non–small-cell lung cancer: a retrospective analysis</p>

Abstract: Introduction: Adjuvant radiotherapy in non-small-cell lung cancer (NSCLC) remains controversial,Whether the mutation status of epidermal growth factor receptor (EGFR) will affect the recurrence and survival of patients with resected NSCLC is rarely reported. Our purpose is to study the effect of postoperative radiotherapy on patients with stage IIIA(N2) NSCLC with EGFR mutation. Methods: Total of of 115 patients diagnosed with stage IIIA(N2) resected NSCLC were analyzed retrospectively. Their EGFR mutations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In all, 20 studies 13,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were finally included after literature screening, including 6 randomized controlled trials and 14 retrospective studies. A total of 6340 patients were enrolled, of which 1972 patients received PORT and 4368 patients did not.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…In all, 20 studies 13,18,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were finally included after literature screening, including 6 randomized controlled trials and 14 retrospective studies. A total of 6340 patients were enrolled, of which 1972 patients received PORT and 4368 patients did not.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“… 14 , 15 , 17 The prognostic significance of EGFR mutation status in patients who underwent PORT was unclear. 18 , 19 In our study, the results revealed that PORT was not associated with better survival outcomes in pⅢA-N2 NSCLC with EGFR mutation, which suggested that targeted therapy may be a more suitable adjuvant treatment option. For EGFR wild-type patients, the options for adjuvant therapies are limited.…”
Section: Discussionmentioning
confidence: 59%
“…11 Some studies demonstrated a possible PORT benefit in specific patient subsets, including pN2 squamous cell cancer 34 and pN2 EGFR-mutant NSCLC. 35 Our study has several limitations inherent in retrospective database methodology. Although we attempted to account for nonrandom selection of patients with PS matching and IPTW, PORT for pN2 NSCLC e14 -Clinical Lung Cancer January 2021 confounding by variables not captured in SEER may exist.…”
Section: Nikhil P Mankuzhy Et Almentioning
confidence: 95%